A Retrospective Analysis of Subaxial Subluxation After Atlanto-axial Arthrodesis in Patients With Rheumatoid Arthritis Based on Annual Radiographs Obtained for 5 Years. Issue 5 (June 2017) - Iizuka, Haku; Iizuka, Yoichi; Mieda, Tokue; Kobayashi, Ryoichi; Nishinome, Masahiro; Ara, Tsuyoshi; Sorimachi, Yasunori; Nakajima, Takashi; Takagishi, Kenji
Abstract : Study Design: Retrospective study. Objective: The purpose of this study was to investigate the incidence of subaxial subluxation (SAS) after atlanto-axial arthrodesis in rheumatoid arthritis (RA) patients using annual radiographs obtained for 5 years and clarify the characteristics of SAS after surgery. Summary of Background Data: Rheumatoid SAS has been reported to occur after atlanto-axial arthrodesis. Many authors have noted that excessive correction of the atlanto-axial angle (AAA) results in a decrease in subaxial lordosis, thereby inducing SAS; therefore, we paid special attention to acquiring a suitable AAA in patients with atlanto-axial arthrodesis. Methods: Twenty-five patients with AAS treated with surgery were reviewed. In all patients, lateral cervical radiographs were obtained in neutral, maximal flexion, and maximal extension positions every year for 5 years after surgery. We investigated the occurrence and progression of SAS using these annual radiographs. Results: There were no significant differences between preoperative and postoperative value in AAA and subaxial angle (SAA), respectively. Before surgery, SAS was found in 10 patients. The occurrence and progression of SAS after surgery was found in 12 cases (SAS P+ group). There were no significant differences in age, sex, or the duration of RA between the SAS P+ group and the remaining 13 cases. We also found no differences in the preoperative and postoperative AAA and SAA between the 2 groups. Conclusions: Although SAA was maintained after atlanto-axial arthrodesis in RA-AAS patients, 12 of 25 patients (48%) with AAS developed SAS after atlanto-axial fusion. Further surgery was not needed for SAS up to 5 years after the initial surgery. We did not find any relationship between the occurrence of SAS and the AAA and SAA before and after surgery. Therefore, our findings suggest that proper reduction of AAA in patients with atlanto-axial arthrodesis does not affect the occurrence of SAS at 5 years after surgery.